Kemeruapan kadar syarat perdagangan dan pertumbuhan: Peranan perbelanjaan fiskal - Jauhari, Azmafazilah; Said, Fathin Faizah; Md. Tahir, Md. Zyadi (Universiti Utara Malaysia, 2005)
This study analysed the correlation between the openness of international trade incorporate size of government spending, implication of stabilisation, and growth of income. Specifically, we analysed the terms of trade volatility that influence the economic growth. We also analysed how government spending has reduced the value of volatility. This research concentrated on samples from the ASEAN-6 countries, which are Philippines, Myanmar, Singapore, Thailand, Malaysia and Indonesia by using 32 years worth of data from the year 1970 to 2002. The ARCH and GARCH (1,1) model estimated were based on the endogenous stochastic growth model. The results show that trade liberalisation increased TOT risk on economic growth and not persistent for the examined countries. In addition, fiscal spending was unable to stabilise income volatility, stimulated by external risk such as trade liberalisation and TOT. Based on the findings, a few policy implications worthy are to be explored.